Pathological Findings in White-Beaked Dolphins (Lagenorhynchus albirostris) and Atlantic White-Sided Dolphins (Lagenorhynchus acutus) From the South-Eastern North Sea - Schick, Luca; IJsseldijk, Lonneke L.; Grilo, Miguel L.; Lakemeyer, Jan; Lehnert, Kristina; Wohlsein, Peter; Ewers, Christa; Prenger-Berninghoff, Ellen; Baumgärtner, Wolfgang; Gröne, Andrea; Kik, Marja J. L.; Siebert, Ursula (Frontiers in Veterinary Science, 2020)
In the North Sea, white-beaked dolphins (Lagenorhynchus albirostris) occur regularly and are the second most common cetacean in the area, while their close relative, the Atlantic white-sided dolphin (Lagenorhynchus acutus), prefers deeper waters of the northern North Sea and adjacent Atlantic Ocean. Strandings of both sepcies have occurred regularly in the past three decades, however, numbers significantly decreased in specifically the southern North Sea more recently. Studies describing necropsy findings in stranded Lagenorhynchus spp. Are, to date, still scarce, while information gained through post-mortem examinations may reveal vital clues about underlying causes of this decline. Therefore, we retrospectively assessed and compared the necropsy results from fresh Lagenorhynchus spp. stranded along the southeastern North Sea between 1990.2019. A full necropsy was performed on 24 white-beaked dolphins and three Atlantic white-sided dolphins. Samples of selected organs were taken for histopathological, bacteriological, mycological, parasitological and virological examinations. The most common findings were emaciation, gastritis and pneumonia. Gastritis and ulceration of the stomach was often associated with a parasitic infection with anisakid nematodes. Pneumonia was most likely appearing due to bacterial infections. Encephalitis was observed in three animals and morbillivirus antigen was detected immunohistochemically in one case. Although the animal also showed pneumonic lesions, virus antigen was only found in the brain. Parasitic infections mainly affected the gastro-intestinal tract. Lungworm infections were only detected in two cases and no association with pathological alterations was observed. Stenurus spp. were identified in two of three cases of parasitic infections of the ears. Twelve of the 26 animals stranded in Germany were found between 1993 and 1994, but there was no evidence on epizootic events or a mass stranding in the monitored period. The main causes of disease and causes of death described will help assessing risk factors, like anthropogenic threats and climate change, and contributes to future conservation of the species.